2012
DOI: 10.1021/jm2017368
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Site-Directed Chemical Modification of Hypocrellins toward Direct Drug Delivery and Effective Photodynamic Activity

Abstract: For photodynamic therapy (PDT) treatment of microvascular diseases, drugs are delivered via blood circulation and the targets are vasculature endothelial cells, for which the contradictory requirements of hydrophilicity and lipophilicity of the drugs have been achieved by liposome preparations. Herein, it is demonstrated that the drug delivery and target affinity are achieved by a single chemical compound, hypocrellin B (HB) derivative 6 selected from three novel aminoalkanesulfonic acid HB derivatives, 5-7. 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…4). 35,64 Interestingly, it was found that the aqueous solubility and PC formed linearly decreasing and increasing sequence with increase in the carbon number, in addition, the singlet oxygen yield increased gradually with the carbon atom number, as shown in Fig. 5.…”
Section: Quantitative and Site-directed Modi¯cation To Optimize The Smentioning
confidence: 87%
See 2 more Smart Citations
“…4). 35,64 Interestingly, it was found that the aqueous solubility and PC formed linearly decreasing and increasing sequence with increase in the carbon number, in addition, the singlet oxygen yield increased gradually with the carbon atom number, as shown in Fig. 5.…”
Section: Quantitative and Site-directed Modi¯cation To Optimize The Smentioning
confidence: 87%
“…Consequently, it exhibited much higher PDT activity to human gastric cancer BGC823 cells than the parent HB, with the IC 50 (de¯ned as the photosensitizer concentration required killing 50% of the cells) of 22 nM compared with that of 40 nM for HB, in addition, it had no dark cellular toxicity. 35 It can be concluded that 6 possesses the optimized amphiphilicity and PDT activity, and can be directly used for intravenous injection without need of preparation of drug-delivery vehicles.…”
Section: Quantitative and Site-directed Modi¯cation To Optimize The Smentioning
confidence: 98%
See 1 more Smart Citation
“…These compounds are isolated from the stromata of Hypocrella bambusae and Shiraia bambusicola . Hypocrellins and their derivatives [ 5 7 ] have gained considerable attentions for two decades, because they can accumulate selectively in cancer cells and their excellent light-induced antiviral activities against tumours and viruses, especially the antiviral activities against the human immunodeficiency virus (HIV) [ 8 ]. In addition to benefiting the pharmaceutical industry, hypocrellins also have extensively potential applications in the agricultural, cosmetic, food, and feed industries [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, HB is a hydrophobic drug and its solubility must be improved in order to maximize its potential bioavailability. One strategy to improve the HB solubility is chemical modification, [28][29][30] but most of the HB derivatives generated to date have exhibited less PDT efficacy than their parent. [31][32][33] This solubility conundrum could be addressed by the use of an alternative pharmaceutical-based strategy.…”
Section: Introductionmentioning
confidence: 99%